PENINGKATAN KEMAMPUAN MENYAMPAIKAN ISI BERITA DI SURAT KABAR MELALUI METODE BERCERITA SISWA KELAS VI SD NEGERI 022 RIMBO PANJANG KECAMATAN TAMBANG - Sarinan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
Upgrades delivering news content on newspaper through storytelling method grade VI Students SD Negeri 022 Rimbo Panjang Kecamatan Tambang. This research is motivated by the lack of ability to deliver the news in the papers third grade students of SD Negeri 022 Rimbo Panjang Kecamatan Tambang. This study aimed to determine whether through the use of story-telling method can improve the ability of students in grade VI SD Negeri 022 Rimbo Panjang Kecamatan Tambang in the field of study to learn to speak Indonesian, which is carried out for 1 month. As the subjects in this study is the sixth grade students in the academic year 2014-2015 the number of students 15 people, consisting of 4 boys and 11 girls. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. According to the research that has been done, then the conclusion to this study about Upgrades deliver the news in a newspaper through storytelling Method Grade III in SD Negeri 022 Rimbo Panjang Kecamatan Tambang. The average value of the ability of students before siklsu I 42.2 in the first cycle, amounting to 63.9 and in the second cycle of 84.2 or capability that is expected to have reached as many as more than 70% of students scored at the top of the KKM is 70. Statements in above shows that the ability to deliver the news in the papers can be enhanced through storytelling.